CCSP SNAA quick reference - Lindfield, Ryan (Cisco Press, 2009)
CCSP SNAA Quick Reference (Digital Short Cut) Ryan Lindfield ISBN-10: 1-58705-877-4 ISBN-13: 978-1-58705-877-6 As a final exam preparation tool, the CCSP SNAA Quick Reference provides a concise review of all objectives on the SNAA exam (642-515). This digital Short Cut provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on configuration and management of the Cisco ASA Security Appliance product. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you focus your study on areas of weakness and to enhance memory retention of essential exam concepts.
Print version record
Keywords: Computer networks -- Security measures; Firewalls (Computer security); Réseaux d'ordinateurs; Sécurité; Mesures; Coupe-feu (Sécurité informatique); Computer networks; Security measures; CCSP; Electronic resource